Performance of Awassi crossbred lambs in farmers flocks of semi-arid region - MAURYA, V P; NAQVI, S M K; MITTAL, J P (The Indian Journal of Animal Sciences, 2013)
A field study was conducted on 55 Awassi crossbred lambs born out of Malpurqa ewes bred artificially using freshly diluted semen of Awassi rams. Their growth and survival rates from birth to 90 days of age were compared with Malpura lambs in the farmers' flocks of a cluster of villages around Avikanagar. Both crossbred and native lambs were kept on identical semi-intensive management throughout the period of this study. The birth weights of male and female crossbred lambs were signicantly higher than birth wrights of their counterpart Malpura lambs. The body weights of these crossbred lambs at the age 90 days were still significantly (P